Les dés sont jetés ! - Pascale Dollfus (Ateliers d'Anthropologie)
Echoing Philippe Sagant’s published writings on play and games, this article shines a light on dice throwing (and its dual language) as practiced today among the nomadic herdsmen of Ladakh, on the fringes of the Tibetan plateau. On these highlands, throwing dice—a gesture always accompanied by equivocal phrases, either murmured to shouted—is not only a method of divination, a pastime or a money game, but also the means of making all decisions relating to the smooth running of the community: choosing the headman and his assistants, dividing up pastures, choosing the men sent to fetch stray animals, etc. This game, open to all men regardless of age and status (layperson or monk, married or single), is not open to women, who are nevertheless exclusively able to reproduce the dice pattern on the wool rugs and blankets they weave, an illustration of the proverb “man of the outside, woman of the inside” that governs society.